Key Assumptions Underlying a Competency-Based Approach to Medical Sciences Education, and Their Applicability to Veterinary Medical Education - Danielson, Jared A. (Frontiers in Veterinary Science, 2021)
This perspective explores six key assumptions of a competency-based approach to medical-sciences based education, as they relate to veterinary medical education. Those assumptions, derived from characteristics of competency based medical education (CBME) identified by CBME proponents are: 1. There are sufficient shortcomings in the medical competence of graduate veterinarians to justify educational change. 2. It is feasible to identify generally accepted core competencies in veterinary medical practice. 3. Teaching to defined learning outcomes will produce greater achievement for learners than approaches that do not emphasize clearly defined outcomes. 4. In veterinary medical education, it is possible to articulate the development of competence sequentially in a manner that is relatively consistent across learners, and carefully planning and sequencing learning activities will produce better learning outcomes. 5. Competency-focused instruction, which tailors the pace and progression of instruction to learners, is feasible in veterinary medical education, and will produce better outcomes than instruction that moves all students through an equivalent process in a set time frame. 6. Programmatic Assessment, including numerous direct observations with feedback, will improve learning outcomes, and is feasible in veterinary medical education. While available research does not unequivocally support all six assumptions, overall the potential benefits of adopting a competency-based approach seem promising for veterinary medical education.